Pharmaceutical interventions in polypharmacy among the elderly and their effects on quality of life (Research, Society and Development, 2025)
This study aimed to conduct an integrative literature review on the effectiveness of pharmacist-led interventions in elderly care, focusing on medication safety, error reduction, and treatment adherence. The analysis showed that pharmacist interventions — such as medication reconciliation, optimization protocols, and electronic prescribing support — significantly reduce inappropriate prescriptions and medication discrepancies, enhancing therapeutic safety and rationality. However, the impact on hard clinical outcomes (mortality, readmissions) remains inconsistent, highlighting the need for more robust studies with longer follow-up. It is concluded that strengthening the pharmacist’s role and adopting electronic decision-support tools are essential strategies to improve pharmacovigilance and patient safety among the elderly within health surveillance systems.